The reliability and accuracy of Polar Team Pro GPS units - Akyildiz, Z.; Yildiz, M.; Clemente, F. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
This study aimed to investigate the accuracy and reliability of Polar Team Pro GPS units (10 Hz) when used to measure distance and total distance covered in different speed zones. Eight amateur soccer players (age: 21.37 ± 1.40 years, height: 176.75 ± 5 cm, body mass: 176.75 ± 9.47 kg) completed a team sport simulation cycle. Two Polar Team Pro GPS units were positioned on each player`s chest, and one GPSports GPS unit (15 Hz) was positioned between the scapulae. The data obtained from the two Polar Team Pro GPS units were compared to determine inter-unit reliability. The data obtained from one of the Polar Team Pro GPS units and the GPSports GPS unit (reference standard) were compared to determine concurrent accuracy. There was acceptable inter-unit reliability of Polar Team Pro GPS units for total distance (TD), low speed running (LSR) (0.00-13.99 km h-1), high speed running (HSR) (14.00-19.99 km h-1) and very high speed running (VHSR) (>20.0 km h-1) with high ICCs (0.63, 0.99, 0.99 and 0.99, respectively), and low typical error of measurement (%) (TEM%) (4.64, 5.05, 1.06 and 2.89, respectively). Regarding accuracy, the ICCs were extremely high for LSR and HSR (0.99 and 0.92, respectively), but high for TD and VHSR (0.63 and 0.65, respectively). Moreover, TEM (%) values were very low for TD and LSR (0.6 and 1.6, respectively), but they were high for HSR and VHSR (13.8 and 13.1, respectively). Consequently, acceptable inter-unit reliability was observed, indicating that the Polar Team Pro GPS unit is suitable for tracking pertinent team-sport variables. Moreover, the Polar Team Pro GPS units (10 Hz) are accurate under the same conditions. However, the research showed that the two systems cannot be used interchangeably for quantifying distances covered at higher speeds.